THE RITUAL OF FIRST INFANT BATHING IN ACEH: An Ethnographic Study in West Labuhan Haji, South Aceh - Abdul Manan (Journal of Contemporary Islam and Muslim Societies, 2019)
Abstrak: Ritual Memandikan Bayi Perdana di Aceh: Studi Etnografi di Labuhan Haji Barat, Aceh Selatan. Kelahiran bayi dianggap sesuatu yang sakral bagi warga Aceh. Beberapa ritual dilakukan untuk menghormati proses tersebut, baik sebelum maupun sesudahnya. Termasuk dalam tujuan ritual adalah menyembuhkan sang ibu yang telah melahirkan secara fisik dan mental. Penelitian ini bertujuan untuk mendeskripsikan ritual memandikan bayi yang dipraktikkan oleh warga Aceh di desa Blangporoh, Aceh Selatan. Pendekatan kualitatif diterapkan dengan wawancara dan pengamatan lapangan sebagai instrumen pengumpul data. Hasil penelitian menunjukkan bahwa komunitas di desa tersebut masih mengaplikasikan ritual memandikan bayi sebagai sebuah simbol menyambut bayi di kalangan mereka. Salah satu ritual mengurbankan seekor kambing jantan, akikah, juga turut dilaksanakan. Kedua ritual tersebut sangat esensial di dalam masyarakat tersebut sebagai salah satu cara memperkenalkan sang bayi terhadap nilai-nilai sosial budaya sejak awal masa kanak-kanak.Kata Kunci: ritual, kelahiran bayi, memandikan bayi, Aceh, IndonesiaAbstract: Childbirth is considered sacred by Acehnese peoples and as such, a newly born baby was introduced to the surrounding world in certain rituals. This is regarded as a re-enactment of the Prophet Muhammad’s actions in the seventh century and a continuation of the village norms to preserve the relations of communications and exchanges across generations. The rituals are conducted to honour this process, before and after it, as well as helping mother to heal the physical and mental condition after labouring. This study aimed to describe the ritual of infant bathing practiced by Acehnese people living in the village of Blangporoh, South Aceh. The qualitative approach was applied as the interviews and field observations were due to collect the data. The result indicated that this community still preserved the ritual of infant bathing as a symbol of welcoming the baby as a way to integrate the baby within society. There was also tradition of the animal sacrifice, Akikah, done along the ritual of infant bathing. The author emphasized that both rituals were important within the society as a way to introducing the baby to socio-cultural values since the early childhood.Keywords: rituals, new-born baby, bathing baby, Aceh, Indonesia